2015
DOI: 10.1038/srep14112
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of ball-milled SrFe12O19 particles consolidated by Spark-Plasma Sintering

Abstract: The room-temperature magnetic properties of ball-milled strontium hexaferrite particles consolidated by spark-plasma sintering are strongly influenced by the milling time. Scanning electron microscopy revealed the ball-milled SrFe12O19 particles to have sizes varying over several hundred nanometers. X-Ray powder-diffraction studies performed on the ball-milled particles before sintering clearly demonstrate the occurrence of a pronounced amorphization process. During sintering at 950 oC, re-crystallization take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 30 publications
5
11
0
Order By: Relevance
“…35,37 For this purpose, milling time was one of the selected processing variables in this study to modify the crystallinity ratio. 38 In accordance with these findings, in this study, nHA-2 was found with 100% crystallinity with the absence of amorphous content, a lower crystallite size, and a higher SSA which is expected to induce better biological responses 39 FIGURE 6. 1 and 2).…”
Section: Modification Of Milling Parameters and Their Importancesupporting
confidence: 84%
See 1 more Smart Citation
“…35,37 For this purpose, milling time was one of the selected processing variables in this study to modify the crystallinity ratio. 38 In accordance with these findings, in this study, nHA-2 was found with 100% crystallinity with the absence of amorphous content, a lower crystallite size, and a higher SSA which is expected to induce better biological responses 39 FIGURE 6. 1 and 2).…”
Section: Modification Of Milling Parameters and Their Importancesupporting
confidence: 84%
“…However, a prolonged ball milling time may adversely affect the degree of crystallinity. 38 In accordance with these findings, in this study, nHA-2 was found with 100% crystallinity with the absence of amorphous content, a lower crystallite size, and a higher SSA which is expected to induce better biological responses 39 FIGURE 6. TGA of different nanoparticles during thermal exposure.…”
Section: Modification Of Milling Parameters and Their Importancesupporting
confidence: 84%
“…The broad and diffuse peaks of Fig. 1 (c-e) once again indicate the tendency of crystalline to amorphous like phase transition [33] of ultrasonically prepared nanoparticles.…”
Section: A Structural Characterizationmentioning
confidence: 93%
“…As a final note, the SPS heating and pressing not only permits to decrease the crystallization/sintering temperatures of hexaferrites and to tailor their magnetic properties, but it also prevents the formation of secondary phases such as α-Fe 2 O 3 [68]. On the other hand, the reductive atmosphere in SPS can lead to hexaferrite decomposition and the subsequent magnetite formation (reduction of Fe 3+ to Fe 2+ ) [69]. Nevertheless, a recent study has shown that such a Fe 3 O 4 secondary phase can be suppressed by using protecting discs of aluminum oxide between the graphite mold and the samples [66].…”
Section: Sps Ofmentioning
confidence: 99%